Application of CT Ultrasonography Combined with Microscopic Intraperitoneal Hyperthermic Perfusion Chemotherapy in Postoperative Treatment of Oocyst Carcinoma. (6th June 2022) - Xia, Zongbao; Jin, Hong
Abstract : For the postoperative treatment of oocyte carcinoma, CT and CT ultrasonography combined with microscopic intraperitoneal should be combined with peritoneal heat perfusion chemotherapy. The authors selected 50 patients who received treatment for ovarian cancer from 2017 to 2018 and divided them into two groups (observation group, 30 cases, control group, 20 cases). Cisplatin, associated with peritoneal hyperthermia, led the control group, and we monitored all patients for 1 year and provided clinical trials, lifestyle, and results for both disease group. The experimental results showed that the target reduction rate of the control group was 70%, while that of the control group was only 40%, lower than that of the control group P < 0.05 . The life expectancy of the control group was higher than that of the control group, P < 0.05 . Nausea, vomiting, diarrhea, bone marrow compression, and constipation in the study group were slightly higher than those in the control group (35%), but there was no significant difference between the two groups (P > 0.05 ). Chemotherapy combined with intraperitoneal infusion of loplatin has no side effects, helps improve survival, and can be used in a variety of clinical trials.